1987
DOI: 10.1111/j.2042-3306.1987.tb01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic dermatitis (sweet itch) of Icelandic horses in Sweden: An epidemiological study

Abstract: Summary A survey of allergic dermatitis (sweet itch) in Sweden contained information on 441 Icelandic horses. Results of a questionnaire indicated that approximately 15 per cent of the country's Icelandic horses suffered from the disease. The prevalence of allergic dermatitis was significantly higher among horses imported from Iceland (26.2 per cent) compared to that of Swedish‐born animals (6.7 per cent). In addition, horses born in Iceland were significantly more severely affected than horses born in Sweden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
71
5
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 19 publications
(22 reference statements)
14
71
5
2
Order By: Relevance
“…This is in agreement with the findings of Braverman et al (1983). Most studies, however, found no clear effect of gender on summer eczema (Broströ m et al, 1987;Halldó rsdó ttir and Larsen, 1991;Lange et al, 2005). Those studies included fewer observations and, in most cases, less even distributions of males and females than in our study.…”
Section: Fixed Effectssupporting
confidence: 86%
See 4 more Smart Citations
“…This is in agreement with the findings of Braverman et al (1983). Most studies, however, found no clear effect of gender on summer eczema (Broströ m et al, 1987;Halldó rsdó ttir and Larsen, 1991;Lange et al, 2005). Those studies included fewer observations and, in most cases, less even distributions of males and females than in our study.…”
Section: Fixed Effectssupporting
confidence: 86%
“…Broströ m et al (1987) found a prevalence of 6.7% among Swedishborn Icelandic horses, and Halldó rsdó ttir and Larsen (1991) reported that 8.2% of Icelandic horses born in Norway were affected by summer eczema. A similar prevalence of 6.3% was reported for Icelandic horses born in Germany, by Reiher and Bjö rnsdó ttir (2004), whereas Lange et al (2005) found a higher prevalence of 16% among German-born Icelandic horses.…”
Section: Prevalencementioning
confidence: 99%
See 3 more Smart Citations